The efficacy and safety of Trilaciclib in preventing chemotherapy-induced myelosuppression: a systematic review and meta-analysis of randomized controlled trials - Qiu, Jingyue; Sheng, Dandan; Lin, Fei; Jiang, Peng; Shi, Ning (Frontiers in Pharmacology, 2023)
Background: This study aims to assess the clinical efficiency and safety of Trilaciclib in preventing chemotherapy-induced myelosuppression in adult patients through meta-analysis. Methods: The PubMed, Embase, Cochrane Library, Clinical Trials, EU Clinical Trials Register, and International Clinical Trials Registry Platform (ICTRP) were searched up to 25 October 2022. Only randomized controlled trials (RCTs) comparing the clinical outcomes of Trilaciclib and Trilaciclib plus chemotherapy for treating malignant cancers in adult patients were included. The primary outcome included the incidence of SN, FN, the DSN, and administration of ESAs, G-CSFs, and RBC or platelet transfusions, while the secondary outcomes included the risk of adverse events (AEs) and severe adverse events (SAEs). Results: In total, four randomized controlled trials (RCTs) involving 345 patients with SCLC or breast cancer were included in this meta-analysis. Results showed that administration of Trilaciclib significantly reduced the occurrence of SN (19.3% vs. 42.2%, OR = 0.31), FN (3.22% vs. 6.72%, OR = 0.47), anemia (20.5% vs. 38.2%, OR = 0.38) and shortened the DSN during treatment. The proportion of patients receiving therapeutic use of ESAs (4.03% vs. 11.8%, OR = 0.31), G-CSF (37.0% vs. 53.5%, OR = 0.52), RBC transfusions (19.8% vs. 29.9%, OR = 0.56) was also statistically lower in the experimental group than in the control group. Meanwhile, the ORR, OS, and PFS of the two groups were identical, and no negative impact of Trilaciclib on the clinical outcomes of chemotherapy treatments was found. Other chemotherapy-induced adverse events (AEs) and severe adverse events (SAEs) like diarrhea, fatigue, nausea, and vomiting were identical regardless of Trilaciclib usage. Conclusion: Trilaciclib demonstrated its efficiency in reducing the occurrence of CIM and utilization of supportive care interventions without undermining the clinical benefits of chemotherapy regimens during treatment with acceptable safety profile.